Towards an Integrated Conceptual Framework of International Business Theory – A Literature Review Perspective: Any Convergence? - Osei-Bonsu, Nana (Archives of Business Research, 2015)
Abstract International business research has tried vividly to advance through several efforts to establish a theoretical base and agreed lines of analysis. The international product life cycle described by Raymond Vernon (1966) probably was the first major theory of the movement of firm’s production overseas, rather than just to explain international trade; since then, several theories have been put forward without any of them gaining acceptance. The theories currently in use in international business research have been borrowed from different disciplines with different views and assumptions underlying their theoretical construct. Each is partial in some significant sense, however, none addresses holistically the essential nature of international business. Therefore, the development of a common theoretical base to provide rich framework to investigate the discipline should be considered among international business scholars and researchers. Key Words International Business, Theories, International Trade, Behavioural theories, Government Policies